Comparative Performance Analysis of Different Routing Protocols in Wireless Ad-hoc networks (IEEE 802.11) - Kumar, Mahendra; Jain, A. K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
Wireless Ad-hoc networks have lack of mass deployment. An Ad hoc wireless network has a dynamic nature that leads to constant changes in its network topology.Â There is an infrastructure less and decentralized network which need a robust dynamic routing protocol. This article presents performance comparison of wireless Ad-hoc network on different routing protocols. Network simulator QualNet 5.0.2 has been used to evaluate the performance of wireless networks with various routing protocols.